A Comparison of ToxCast Test Results with In Vivo and Other In Vitro Endpoints for Neuro, Endocrine, and Developmental Toxicities: A Case Study Using Endosulfan and Methidathion. (27th May 2015) - Silva, M.; Pham, N.; Lewis, C.; Iyer, S.; Kwok, E.; Solomon, G.; Zeise, L.
<x xml:space="preserve">Abstract</x> INTRODUCTION The U.S. Environmental Protection Agency's (EPA's) Toxicity Forecaster (ToxCast) is a potential tool for chemical prioritization, hazard identification, and risk assessment. We conducted a case study to compare ToxCast data with endpoints from other in vitro and in vivo studies for two data‐rich pesticides: endosulfan and methidathion. METHODS ToxCast assays for endocrine disruption, development (zebrafish), and neurotoxicity were qualitatively compared to traditional neurotoxicity, developmental and reproductive toxicity findings. We also used in vitro–in vivo extrapolation to convert half‐maximal activity concentrations in active ToxCast assays to rat oral equivalent doses, and quantitatively compared these to the lowest observable effect level (LOEL) from in vivo studies. RESULTS Endosulfan was inactive for GABAAR, unlike in vivo; but active with dopamine transporter assays and was neurotoxic in zebrafish as expected. Methidathion was not active for these endpoints in vivo or in vitro. Acetylcholinesterase inhibition was ToxCast‐inactive, although both pesticides are inhibitors in vivo. ToxCast results were generally inactive for endosulfan estrogen receptor agonism and androgen receptor antagonism unlike in vivo. Calculated oral equivalent doses for estrogen receptor and androgen receptor pathways and for zebrafish assays for both compounds were generally consistent with in vivo LOELs. Endosulfan showed neurotoxicity and both pesticides showed developmental effects in the zebrafish assays, although methidathion is not developmentally toxic in vivo. CONCLUSIONS ToxCast's predictions showed concordance on some endpoints and nonconcordance, consisting mainly of false inactives, in several critical endpoints, likely due to a lack of metabolic activation and limitations in assay design. Zebrafish assays were good predictors of developmental toxicity and neurotoxicity for endosulfan